Epidemiologic Characteristics of ESBL-Producing ST131 E. coli Identified Through the Emerging Infections Program, 2017. (October 2020) - Duffy, Nadezhda; Campbell, Davina; Reses, Hannah E.; Basiliere, Elizabeth; Bower, Chris; Dumyati, Ghinwa; Kainer, Marion; Muleta, Daniel; Byrd-Warner, Benji; Stanton, Richard; Daniels, Jonathan; Halpin, Alison; et al.
Abstract : Background: Extended-spectrum β-lactamase–producing (ESBL) Escherichia coli infection incidence is increasing in the United States. This increase may be due to the rapid expansion of ST131, which is now the predominant ESBL strain globally, often multidrug resistant, and has been shown to establish longer-term human colonization than other E. coli strains. We assessed potential risk factors that distinguish ST131 from other ESBL E. coli . Methods: From October 1 through December 31, 2017, 5 CDC Emerging Infections Program (EIP) sites pilot tested active, laboratory-based surveillance in selected counties in Colorado, Georgia, New Mexico, New York, and Tennessee. An E. coli case was defined as the first isolation from a normally sterile body site or urine in a surveillance area resident in a 30-day period resistant to 1 extended-spectrum cephalosporin antibiotic and susceptible or intermediate to all carbapenem antibiotics tested. Epidemiologic data were collected from case patients' medical records. A convenience sample of 117 E. coli isolates from case patients was collected. All isolates underwent whole-genome sequencing to determine sequence type and the presence of ESBL genes. We compared ST131 E. coli epidemiology to other ESBL E. coli . Results: Among 117 E. coli isolates, 97 (83%) were ESBL producers. Of the 97 ESBL E. coli, 52 (54%) were ST131 (range, for 4 EIP sites submitting >10 isolates: 25%–88%; P < .001). Other common STs were ST38 (12%) and ST10 (5%). ST131 infections were more likely to be healthcare-associated than non-ST131 (56% vs 36%; P = .05) (Table 1). Among specific prior healthcare exposures, only residence in long-term care facilities (LTCFs) in the year before culture was more common among ST131 case patients (29% vs 11%; P = .03). Notably, 85% of ESBL E. coli collected from LTCF residents were ST131. ST131 E. coli were more common among patients with underlying medical conditions (81% vs 60%; P = .02). No statistically significant difference by sex, race, age, culture source, location of culture collection, and frequency of antibiotic use in the prior 30 days was observed. Conclusions: The prevalence of ST131 E. coli varies regionally. The association between ST131 and LTCFs suggests that these may be particularly important settings for ST131 acquisition. Improving infection control measures that limit ESBL transmission in these settings and preventing dissemination in facilities receiving patients from LTCFs may be necessary to contain ST131 spread. Funding: None Disclosures: None